Causes of Construction Wastes and Capabilities of Building Information Modelling (BIM) in Minimizing the Wastes - Kong, Sio Kah; Tiew, Ying Lou; Lee, Benny, Hai Chim (INTI International University, 2020)
Recently the amount of Construction and Demolition (C&D) wastes generated in Malaysia is enormous due to the rapid development. Malaysian Government carried out many efforts to reduce the generation of construction wastes by implementing policy for the contractor to comply. Regrettably, it does not reach the level of effectiveness required in reducing the construction wastes. The generation of C&D wastes not only affect the cost of a project but also lead to many environmental impacts such as air and water pollution. BIM is a 3D model-based process to create and manage information on a construction project on a project throughout the entire project lifecycle. It allows the project participates working together in the planning, design and construction of a building in one 3D model thereby manage and minimize C&D wastes efficiently. The aim of this research is to explore the causes of construction wastes and the capabilities of BIM in minimizing the wastes. This research is targeted to the Quantity Surveyors in Kuala Lumpur and the method used to collect primary data is quantitative questionnaire. The collected primary data is then analysed by using Relative Importance Index (RII) and Mean Score (MS) method. The results revealed that poor planning and low rate of reuse and recycling of wastes is the most significant causes of construction wastes while accurate quantity take-off is the most effective capability of BIM in minimizing these wastes.